A rare case of early onset lewy body dementia with parkinsonism associated with chronic exposure to copper contaminated drinking water - Ratner, Marcia H.; Rutchik, Jonathan S. (Frontiers in Toxicology, 2024)
There is a well-recognized relationship between a person’s body burden of essential trace elements such as copper and their neurological function in which both deficiencies and exposures to excessive concentrations are associated with adverse clinical outcomes. Preclinical studies indicate chronic excess copper exposure is associated with altered motor function, dopaminergic neuronal loss, astrocytosis, and microgliosis. Copper also promotes oligomerization and fibrilization of α-synuclein suggesting it may hasten the course of an α-synucleinopathy. Here we report a rare case of early onset Lewy Body Dementia with Parkinsonism in a 53-year-old Caucasian woman exposed to copper contaminated drinking water for more than 10 years. Her hair and that of her daughter had streaks of blue-green discoloration as did the porcelain sinks in their home. Testing confirmed copper contamination of the drinking water. A neurologist diagnosed her with Lewy Body Dementia with Parkinsonism. Skin biopsy for phosphorylated α was consistent with a diagnosis of an α-synucleinopathy. These findings suggest chronic exposure to excessive copper may act as disease modifying factor in Lewy Body Dementia with Parkinsonism. It has previously been recommended that individuals at risk of Alzheimer’s disease (AD) avoid excessive intake of copper. Genetic studies indicate that Lewy Body Dementia shares risk factors and pathways with AD. Based on the observations in this patient we recommend that individuals at risk for an α-synucleinopathy based on a positive family history, genetic testing, and/or positive results on a skin biopsy for phosphorylated α-synuclein avoid exposure to excess copper.